Impacts of Paraburkholderia phytofirmans Strain PsJN on Tomato (Lycopersicon esculentum L.) Under High Temperature - Issa, Alaa; Esmaeel, Qassim; Sanchez, Lisa; Courteaux, Barbara; Guise, Jean-Francois; Gibon, Yves; Ballias, Patricia; Clément, Christophe; Jacquard, Cédric; Vaillant-Gaveau, Nathalie; Aït Barka, Essaïd (Frontiers in Plant Science, 2018)
Abnormal temperatures induce physiological and biochemical changes resulting in the loss of yield. The present study investigates the impact of the PsJN strain of Paraburkholderia phytofirmans on tomato (Lycopersicon esculentum Mill.) in response to heat stress (32°C). The results of this work showed that bacterial inoculation with P. phytofirmans strain PsJN increased tomato growth parameters such as chlorophyll content and gas exchange at both normal and high temperatures (25 and 32°C). At normal temperature (25°C), the rate of photosynthesis and the photosystem II activity increased with significant accumulations of sugars, total amino acids, proline, and malate in the bacterized tomato plants, demonstrating that the PsJN strain had a positive effect on plant growth. However, the amount of sucrose, total amino acids, proline, and malate were significantly affected in tomato leaves at 32°C compared to that at 25°C. Changes in photosynthesis and chlorophyll fluorescence showed that the bacterized tomato plants were well acclimated at 32°C. These results reinforce the current knowledge about the PsJN strain of P. phytofirmans and highlight in particular its ability to alleviate the harmful effects of high temperatures by stimulating the growth and tolerance of tomato plants.